Cost‐effectiveness analysis of ovarian tissue cryopreservation and transplantation for preservation of fertility in post‐pubertal oncological women submitted to high‐risk gonadotoxic chemotherapy. Issue 1 (17th February 2022) - Raimondo, Diego; Giaquinto, Ilaria; Maletta, Manuela; Vicenti, Rossella; Iodice, Raffaella; Arena, Alessandro; Del Forno, Simona; Raffone, Antonio; Lenzi, Jacopo; Casadio, Paolo; Seracchioli, Renato
Abstract: Objective: To study the economic impact of ovarian tissue cryopreservation and transplantation (OTC) in post‐pubertal patients who underwent high‐risk gonadotoxic chemotherapy. Methods: A decision tree model was used to determine the live birth rate and cost‐effectiveness of OTC versus non‐OTC. The incremental cost‐effectiveness ratio (ICER) was calculated. A sensitivity analysis was performed under the assumption that the costs of ovarian cortex retrieval, cryopreservation, and storage for patients with cancer might be covered by the national health system or health insurance. Results: Patients had the greatest probability of achieving live birth after high‐risk chemotherapy when they underwent OTC versus non‐OTC. Although cryopreservation of ovarian tissue results in higher live birth rates, it is always more expensive. Cost‐effectiveness increases when the majority of patients completes the path of tissue cryopreservation plus transplantation after 5 years. Conclusion: Although OCT has been demonstrated as a procedure for effective fertility preservation in fertility‐age women with cancer, no cost‐effectiveness analysis has been performed until now. This model could help healthcare systems to allocate coverage for OCT. Abstract : The contents of this page will be used as part of issue TOC only. It will not be published as part of main article.This model could help practitioners facilitating counseling about cost and outcomes associated with cryopreservation and transplantation of ovarian tissue and healthcare systems allocating coverage for this program.